2015
DOI: 10.1016/j.annepidem.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behavior and all-cause mortality among blacks and whites with diabetes

Abstract: Purpose The study objective was to examine the role of physical activity (PA) and sedentary time (ST) on mortality risk among a population of low-income adults with diabetes. Methods Black (n = 11,137) and white (n = 4508) men and women with diabetes from the Southern Community Cohort Study self-reported total PA levels and total ST. Participants were categorized into quartiles of total PA and total ST. Hazard ratios (HRs) and 95% confidence intervals (CIs) for subsequent mortality risk were estimated from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Ten studies[5160] assessed disparities in exercise or physical activity, with seven[52–56; 58; 59] assessing adjusted disparities. Studies reporting NHBs performed less physical activity than NHWs showed small disparities that became nonsignificant after adjustment for covariates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies[5160] assessed disparities in exercise or physical activity, with seven[52–56; 58; 59] assessing adjusted disparities. Studies reporting NHBs performed less physical activity than NHWs showed small disparities that became nonsignificant after adjustment for covariates.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting NHBs performed less physical activity than NHWs showed small disparities that became nonsignificant after adjustment for covariates. [55; 58; 60] No studies found a significant disparity between Hispanics and NHBs. Evidence of a disparity in physical activity between Hispanics and NHWs was mixed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations